1971
DOI: 10.2307/1142178
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation and Aggressive Behavior in a Correctional Center for Women

Abstract: The belief that a menstruating woman may have harmful effects on others is not novel, nor is it confined to any particular type of society.' Almost two thousand years ago the Roman naturalist Pliny argued for the seclusion of menstruating women on the grounds that menstrual blood could, among other things, "dull a razor ... kill a swarm of bees ... make men lose their strength and ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Despite the prevalence of these beliefs, there are only a few empirical studies providing support for this relationship between the menstrual cycle and aggressive, criminal, and other antisocial behaviors [Cowen, 1994;Horney, 1978]. While the early studies in this area have been criticized for their methodological problems [see Harry and Balcer, 1987], more recent studies have provided limited evidence for a relationship between aggression and menstrual cycle phase [Clare, 1985;d'Orban and Dalton, 1980;Ellis and Austin, 1971]. Dalton [1964] was one of the first researchers to study the relationship between crime and menstruation.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the prevalence of these beliefs, there are only a few empirical studies providing support for this relationship between the menstrual cycle and aggressive, criminal, and other antisocial behaviors [Cowen, 1994;Horney, 1978]. While the early studies in this area have been criticized for their methodological problems [see Harry and Balcer, 1987], more recent studies have provided limited evidence for a relationship between aggression and menstrual cycle phase [Clare, 1985;d'Orban and Dalton, 1980;Ellis and Austin, 1971]. Dalton [1964] was one of the first researchers to study the relationship between crime and menstruation.…”
Section: Introductionmentioning
confidence: 97%
“…Since the description of the premenstrual tension syndrome by Frank (1931), there have been a number of studies on the relationship between phases of the menstrual cycle and behaviour in female offenders. Most investigators were concerned with women's behaviour in penal institutions (Dalton, 1961;Ellis & Austin, 1971) or in a special hospital (Hands et al 1974) and showed that female offenders were more liable to aggressive behaviour during the premenstrual and menstrual phases of their cycle. Morton et al (1953) reported that the treatment of premenstrual tension in female prisoners resulted in improved behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Most writers on the subject have related the presumption to a theory of hormonal effects on behaviour. An association of violence and behavioural disorders with the premenstrual days has been proposed (Ellis & Austin, 1971) and sexual desire and sexual behaviour have been associated with menstrual rhythms (Udry & Morris, 1968). Other emotional states have been shown to vary according to menstrual patterns (Moos et al, 1969).…”
Section: Introductionmentioning
confidence: 99%